3.8k views
0 votes
A student solved the equation 7 = 3(t - 1) - 2(t - 3) as shown below. Assume there is a value for t that satisfies the equation. Provide a justification for each step of the solution process. LaTeX: 7\:=\:3\left(t-1\right)-2\left(t-3\right)7 = 3 ( t − 1 ) − 2 ( t − 3 ) LaTeX: 7\:=\:3t\:-3-2t\:+67 = 3 t − 3 − 2 t + 6.

User Sweets
by
5.0k points

1 Answer

3 votes

Answer: 7

Step-by-step explanation: You first distribute 3, and -2. This gets you 7 = 3t -3 -2t +3. Then you add like terms which gets you, 7 = t.

User Vitalii Boiarskyi
by
4.7k points